2015
DOI: 10.1016/j.numecd.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Healthy eating and survival among elderly men with and without cardiovascular-metabolic diseases

Abstract: A high quality diet was associated with a 40% lower mortality risk and 2.5 years longer life expectancy in elderly men with, but not without, cardiovascular-metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…After dual screening, 11 547 relevant studies were identified. The body of evidence included 153 articles (involving 6 550 664 individuals), of which 1 was from a randomized clinical trial (RCT) and 152 were from observational studies(Figure 2). Multiple articles used data from the same study but used different methods or represented unique subsamples or dietary patterns.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…After dual screening, 11 547 relevant studies were identified. The body of evidence included 153 articles (involving 6 550 664 individuals), of which 1 was from a randomized clinical trial (RCT) and 152 were from observational studies(Figure 2). Multiple articles used data from the same study but used different methods or represented unique subsamples or dietary patterns.…”
Section: Resultsmentioning
confidence: 66%
“…Fifty-three studies originated from the US. Some studies exclusively enrolled female or male participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 A better diet quality can decrease mortality risk by 40% and prolong life expectancy by 2.5 years in elderly patients with cardiovascular disease. 21 However, this association was not statistically significant in healthy subjects. Moreover, a higher diet quality score was found in elderly patients with cardiovascular disease than in healthy elderly individuals.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, a higher diet quality score was found in elderly patients with cardiovascular disease than in healthy elderly individuals. 21 These findings were attributed to the fact that 17% of healthy elderly patients versus more than half (54%) of the elderly patients with cardiovascular disease followed a prescribed eating plan. In our sample, all patients had cardiovascular disease; however, when stratified by the presence or absence of diabetes, there was a difference in diet quality.…”
Section: Discussionmentioning
confidence: 99%